A visit of an anxious patient: A review - Elena S. Akarachkova; Lidiia R. Kadyrova; Leonid V. Klimov; Artem A. Kondrashov; Olga V. Kotova; Dzhinna I. Lebedeva (Consilium Medicum, 2024)
In the article, the authors answered the following questions: How often do anxious patients occur in clinical practice? Why do most patients with anxiety see primary care physicians rather than a psychiatrist? What complaints and manifestations help to suspect anxiety in the patient? How can a non-psychiatrist identify and diagnose anxiety? How to manage a patient with diagnosed anxiety? Short-term and long-term outcomes/prognosis.